European Cities of Sport as a Strategic Policy for Local Development of Sports: A Perspective from Sports Management in the Last Decade - Teixeira, Mário Coelho (2024)
European sports policies have focused on the implementation of public instruments and policy measures, aiming to encourage EU member states to promote and improve sports habits, while simultaneously tackling high levels of sedentary lifestyle among Europeans. Despite these efforts, data concerning the various measures is quite limited, making it impossible to assess the real impact on the population, particularly in the case of the European Cities of Sport. This award has been held since 2007 and has already distinguished 193 cities; however, current knowledge does not allow researchers to theorise about its multiple impacts as a strategic policy instrument for the local development of sport in Europe, thus constituting a gap within sports management research. In order to further this knowledge, we explored European reality over a decade (2013–2022), analysing nine awards of Portuguese cities. We employed qualitative methods for documentary analysis of public information and descriptive statistics for data analysis. The results show that over 2 600 multidisciplinary events were organised, among which 402 had an international character (15%), an average of 50 sports disciplines per edition, 359 events related to culture and education, and involved over 1 000 000 participants, with an overall investment of over €39 million. This research now allows a theoretical-scientific and operational referential pattern of key indicators to be established for future European ECS applications, while demonstrating an encouraging relationship, from a sports perspective and economically, between public investment made and estimated return, thus contributing to better political decisions and to the positive implications of increasing public investment in sport.